2021
DOI: 10.2147/rru.s324786
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cortical Thickness After Pyeloplasty in Pediatric Ureteropelvic Junction Obstruction

Abstract: Purpose: The main goal of pyeloplasty is to maintain or improve renal function. Diuretic renography is the gold standard for evaluating renal function after pyeloplasty. Renal ultrasonography (RUS) is commonly used to determine hydronephrosis in pediatric patients. We hypothesized that the change in the renal parenchymal cortex would predict pyeloplasty success. In this study, we aim to measure renal cortical thickness change after pyeloplasty in ureteropelvic junction obstruction patients. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In children, it was shown that renal parenchymal thickness increases after pyeloplasty. 31 We detected a significant decrease in hydronephrosis and a significant increase in parenchymal thickness after pyeloplasty in adults. In the study of Isoyama et al, it was reported that in 73% of the cases one grade of improvement, and in 27% of the cases 2 grades of improvement in hydronephrosis were detected 6 months after the surgery.…”
Section: Discussionmentioning
confidence: 64%
“…In children, it was shown that renal parenchymal thickness increases after pyeloplasty. 31 We detected a significant decrease in hydronephrosis and a significant increase in parenchymal thickness after pyeloplasty in adults. In the study of Isoyama et al, it was reported that in 73% of the cases one grade of improvement, and in 27% of the cases 2 grades of improvement in hydronephrosis were detected 6 months after the surgery.…”
Section: Discussionmentioning
confidence: 64%
“…Others have proposed combining US parameters together to obtain better outcome. Parenchymal/ cortical thickness is not affected by surgery itself and shows improvements after surgery [13,14]. PCR combines parenchymal thickness with degree of hydronephrosis, while CPR has the advantage of both parameters are not being directly manipulated by surgery.…”
Section: Discussionmentioning
confidence: 99%